Formation of public-private model in Russia health care organization - V. I. Perkhov (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
The pandemic of COVID-19, the threat of technogenic and anthropogenic character, brought to the foreground non-market aspects of the general, corporate branch culture and strategy in medicine and health care. Therefore, in many countries, despite differences in state and private property ratios in health infrastructure, the state priority is ensuring cooperation within the national health care system which capable quickly and well-coordinated work in the extremely dangerous epidemics conditions and other emergency situations. The purpose of this article is discussing a problem of public and private models of medical care organization in Russian health care system.Materials and methods. Content analysis methods, economical and statistical analysis, information and analytical materials of the Russian and foreign news agencies, a summary across Russia of Rosstat form No. 62 of the state statistical observation «Data on resource providing and on delivery of health care to the population» (legal entities - the medical organizations which are carrying out activity in the sphere of compulsory health insurance), analytical materials and statistical data of World Health Organization (The European portal of information of health care of WHO: https://gateway.euro.who.int/en/hfa-explorer/), statistical data and metadata on the countries of the Organization for Economic Cooperation and Development (OECD, https://stats.oecd.org/), the materials of monographic researches and periodicals including placed on the Internet were used in this article.Results: the system of compulsory health insurance is an ancestor of the program of the state guarantees of free medical care of in Russian citizens. The length of the text of this Program so far was increased in 130 times in comparison with initial edition of 1998. At the same time, there is still no clear delineation for the bases, volumes and conditions differentiation of free and paid medical care rendering. As a result, the major human right to free medical care remains not completely realized. The numbers of the non-state medical organizations to provide free of charge medical care to the population according to the policy of obligatory medical insurance (i.e. financed from the state sources) in the period of 2011 to 2019 – from 648 to 2423 organizations respectively were increased in Russia four times. This demonstrates the creation of the new, «integrated» model of health care in Russia in the mode of public and private partnership for deciding of social tasks. Although, free medical care for citizens in the private medical organizations is not mentioned in the Constitution of Russian Federation (Main Law). In emergency situations such integration allows private medical structures to involve capacities and also be coordinated with one of the tasks of the Ministry of health target program «Development of the Fundamental, Transmitting and Personalized Medicine».Conclusions. There is a formation of the integrated, public and private (hybrid) model of health care in modern Russia that needs developing of a new partnership and principles of management in the sphere of medical care organization. State policy in the health care financing sphere should be directed not only to the state guarantees of medical care specification, but also to a gap in social and economic inequality reduction. The social protection systems should be focused, first of all, on people who are most in great need of medical care. For the protecting population from catastrophic payments for medical care, it is necessary to bring the concept of the social standards - a number of the general rules, norms and standards which must guarantee the state ensuring constitutional rights of citizens to free medical care in the health care legislation.